A Complex Mix of Confidence, Uncertainty, and Struggle: Korean Secondary Social Studies Teachers’ Perspectives and Practice on Multiculturalism - Kim, Eunjung (International Journal of Multicultural Education, 2022)
This study examines perspectives and practices regarding multiculturalism among 20 secondary social studies teachers in South Korea. Utilizing semi-structured interviews and critical discourse analysis, the study seeks to capture how teachers’ understandings of multiculturalism (Damunhwa in Korean) and its practice are influenced by curriculum changes, interactions with Damunhwa students, school duties, and personal experiences. The study finds that teachers know curriculum changes clearly, have little understanding of Damunhwa students, and experience discrepancies between high intellectual recognition of multiculturalism and their own ingrained biases.